1990-ээд оны бичиг үсэг солих хөдөлгөөн, түүний сургамж: Literacy movement of 1990s and its remark - Уриа (Mongolian Studies, 2023)
The article deals with the measures that were taken to prepare for the official transition from Cyrillic to Mongolian script in the early 1990’s, and its implementation, and also analyzes the officials’ views of that period on the event. Moreover, he explains the result of his study explaining theoretical principles mentioned by the previous scholars.